Transforming anion instability into stability: contrasting photoionization of three protonation forms of the phosphate ion upon moving into water - Pluhařová, Eva; Ončák, Milan; Seidel, Robert; Schroeder, Christi; Schroeder, William; Winter, Bernd; Bradforth, Stephen E; Jungwirth, Pavel; Slavíček, Petr (The journal of physical chemistry. B, 2012)
We use photoelectron emission spectroscopy with vacuum microjet technique and quantum chemistry calculations to investigate electronic structure and stability of aqueous phosphate anions. On the basis of the measured photoelectron spectra of sodium phosphates at different pH, we report the lowest vertical ionization energies of monobasic (9.5 eV), dibasic (8.9 eV), and tribasic (8.4 eV) anions. Electron binding energies were in tandem modeled with ab initio methods, using a mixed dielectric solvation model together with up to 64 explicitly solvating water molecules. We demonstrate that two solvation layers of explicit water molecules are needed to obtain converged values of vertical ionization energies (VIEs) within this mixed solvation model, leading to very good agreement with experiment. We also show that the highly charged PO(4)(3-) anion, which is electronically unstable in the gas phase, gains the electronic stability with about 16 water molecules, while only 2-3 water molecules are sufficient to stabilize the doubly charged phosphate anion. We also investigate the effect of ion pairing on the vertical ionization energy. In contrast to protonation (leading to a formation of covalent O-H bond), sodiation (leading to an anion···Na(+) ion pair) has only a weak effect on the electron binding energy.